Parents' experiences of information and communication in the neonatal unit about brain imaging and neurological prognosis: A qualitative study - Harvey, M; Nongena, P; Gonzalez-Cinca, N; Edwards, A; Redshaw, M (2013)
Aim To explore parental information and communication needs during their baby's care in the neonatal unit with a focus on brain imaging and neurological prognosis. Methods Eighteen parents recruited from one neonatal unit in the United Kingdom participated in semi-structured qualitative interviews using a grounded theory approach. The topic guide focused on information received about neonatal brain imaging, diagnosis and prognosis, emotional impact and support. Results Parents expressed different information needs influenced by their history, expectations, coping strategies and experiences. Most felt they initially were passive recipients of information and attempted to gain control of the information flow. Nurses were the main providers of information; doctors and other parents were also valuable. Attending ward rounds was important. Some parents felt accessing specific information such as the results of brain imaging could be difficult. Concerns about long-term developmental outcomes and the need for information did not diminish over time. The emotional impact of having a preterm baby had a negative effect on parents' ability to retain information, and all had an ongoing need for reassurance. Conclusion The findings provide insights about the needs and experiences of parents who have a continuing requirement for information about their infant's care, development and prognosis. ©2013 The Author(s)/Acta Pædiatrica ©2013 Foundation Acta Pædiatrica.